2024
DOI: 10.1523/eneuro.0362-23.2024
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Circuit Hyperexcitability in Mouse Neocortical Slice Cultures with Increasing Duration of Activity Silencing

Derek L. Wise,
Samuel B. Greene,
Yasmin Escobedo-Lozoya
et al.

Abstract: Forebrain neurons deprived of activity become hyperactive when activity is restored. Rebound activity has been linked to spontaneous seizures in vivo following prolonged activity blockade. Here we measured the time course of rebound activity and the contributing circuit mechanisms using calcium imaging, synaptic staining, and whole cell patch clamp in organotypic slice cultures of mouse neocortex. Calcium imaging revealed hypersynchronous activity increasing in intensity with longer periods of deprivation. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The results of this and other recent studies employing activity manipulations in slice cultures ( Valakh et al, 2023 ; Wise et al, 2024 ) reveal that most of the homeostatic mechanisms identified in prior studies of dissociated cultures, including increased intrinsic excitability, changes in inhibition, and pre- and postsynaptic changes in excitatory synaptic transmission can be readily studied in this more intact preparation in which many histological and anatomical features of cortical circuits are preserved but which are broadly amenable to pharmacological and genetic manipulation. This may provide a useful platform for identifying candidate molecules involved in the signal transduction pathways and transcriptional networks regulating homeostatic plasticity.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The results of this and other recent studies employing activity manipulations in slice cultures ( Valakh et al, 2023 ; Wise et al, 2024 ) reveal that most of the homeostatic mechanisms identified in prior studies of dissociated cultures, including increased intrinsic excitability, changes in inhibition, and pre- and postsynaptic changes in excitatory synaptic transmission can be readily studied in this more intact preparation in which many histological and anatomical features of cortical circuits are preserved but which are broadly amenable to pharmacological and genetic manipulation. This may provide a useful platform for identifying candidate molecules involved in the signal transduction pathways and transcriptional networks regulating homeostatic plasticity.…”
Section: Discussionmentioning
confidence: 64%
“…The loss of excitatory synapses may reflect an inability to maintain transient synapses under silenced conditions when coincident firing cannot contribute to stabilization ( Hedrick et al, 2024 ). Nevertheless, the presence of rebound hyperexcitability measured previously in cultures subjected to the same activity deprivation ( Koch et al, 2010 ; Wise et al, 2024 ) suggests the reductions in synapse number are not sufficient to overcome other changes in circuit excitability, including the observed increases in excitatory synaptic strength.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations